PEDAGOGICAL PRINCIPLES OF USING THE DUAL EDUCATION SYSTEM IN THE TRAINING OF SPECIALIST PERSONNEL IN THE EDUCATIONAL SYSTEM. (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2024)
in this article, we aim to create wide opportunities for training middle-level personnel with qualified and modern professional skills in all areas of the economy, and to support the interests of young people in acquiring professions and specialties.